Рыбы (Pisces) малых рек Правобережного Полесья УССР. Сообщение III. Видовой состав рыбного населения правобережных притоков нижнего течения Припяти и Среднего Днепра - Полтавчук, М.А. (Вестник зоологии, 1976)
The communication deals with the data on species composition, distribution and interspecies numerical ratio of fishes in the Uzh, Teterev and Irpen rivers by biotopes. Indexes of linear dimensions of fingerlings in each of the examined rivers are presented.